Impact of Transformational Leadership on Constructive Deviant Behaviors: The Mediating Role of Felt Obligation - Lalarukh Shabbir; Muhammad Hassan (iRASD Journal of Management)
The primary goal of this research is to determine the influence of transformational leadership on constructive deviant behaviors (pro-social behavior, expressing voice, taking charge, whistleblowing) with the mediating effect of felt obligation. Diverse sample (IT, banking, and health) was taken for the data collection. Data was collected through questionnaires. Data was collected in three different time lags. The result of this study showed that transformational leadership has a significant influence on constructive deviant behaviors. The findings also show that the association between transformational leadership and constructive deviant behaviors is mediated by felt obligation. The association between felt obligation and constructive deviant actions is also strongly moderated by challenge stressor.